2005
DOI: 10.1115/1.1789516
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Surface and Interior Combustion Using Composite Porous Inert Media

Abstract: Combustion using silicon carbide coated, carbon–carbon composite porous inert media (PIM) was investigated. Two combustion modes, surface and interior, depending upon the location of flame stabilization, were considered. Combustion performance was evaluated by measurements of pressure drop across the PIM, emissions of NOx and CO, and the lean blow-off limit. Data were obtained for the two combustion modes at identical conditions for a range of reactant flowrates, equivalence ratios, and pore sizes of the PIM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…Coating of carbon foams with reinforcing material can potentially eliminate cracking and achieve high structural strength in PMBs. Studies using coated carbon foams have successfully achieved combustion without incurring material degradation [12,29].…”
Section: Durability Testingmentioning
confidence: 99%
“…Coating of carbon foams with reinforcing material can potentially eliminate cracking and achieve high structural strength in PMBs. Studies using coated carbon foams have successfully achieved combustion without incurring material degradation [12,29].…”
Section: Durability Testingmentioning
confidence: 99%
“…Flow resistance associated with the PIM was modeled by sink terms in the momentum conservation equations. The sink term is expressed as a power law correlation with experimentally determined coefficients [25]. An effective thermal conductivity was used to account for the solid and fluid thermal conductivities weighted by the porosity of the PIM.…”
Section: Cfd Analysismentioning
confidence: 99%
“…The pore density is specified in terms of pores per inch or pores per centimeter (ppcm). Porosity and pore density affect the flow resistance or pressure drop across the porous material [25].…”
Section: Introductionmentioning
confidence: 99%
“…Both porosity and pore density of the insert affect the flow structure and pressure drop across the PIM [28], Marbach and Agrawal [28] have also demonstrated that PIM can be used to extend the lean blow-off limit. 137, APRIL 2015 state of the art 3D manufacturing techniques.…”
Section: (A ) S C H E M a T Ic D Ia G R A M A N D (B) P H O T O G R Amentioning
confidence: 99%